Preparation method and application of metal organic framework nanosheet
Through solvent thermal synthesis and physical peeling technology on 3D MOFs, high catalytic activity metal organic frame nanosheets were prepared, which solved the problems of pore size limitation and slow electron transfer in the catalytic inert C(sp3)-H bond oxidation of 3D MOFs, and achieved efficient catalytic coupling reaction between cyclohexane and benzylene malonitrile and the aerobic oxidation reaction of cyclohexane.
Patent Information
- Application Number
- CN202411440819.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-05-17
- Filing Date
- 2024-10-16
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The existing 3D metal organic frameworks (MOFs) have problems such as pore size limitation, slow electron transfer and substrate diffusion during the oxidation of catalytically inert C(sp3)-H bonds, resulting in insufficient photocatalytic activity.
Three-dimensional layered metal-organic frame materials were constructed through solvent thermal synthesis strategy, and high catalytic activity metal-organic frame nanosheets were prepared using physical peeling technology. The nanosheet uses the transition metal ion Cu2+ as the node and uses 2,7-dicarboxyanthraquinone as the ligand to form a stable network structure, providing more active sites and oxygen adsorption centers.
The catalytic activity is improved, and the coupling reaction between cyclohexane and benzylene malonitrile and the aerobic oxidation reaction of cyclohexane is efficiently catalyzed under mild light conditions, with significantly improved yield and selectivity.
Smart Images

Figure CN119570049A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of a metal organic framework nanosheet and application thereof, belonging to the technical field of metal organic framework catalytic materials. Background Art
[0002] As the most basic structural unit, C(sp 3 )-H bonds exist in almost all organic compounds. 3 )−H bonds can directly convert low-cost industrial raw materials into high-value fine chemicals, which has attracted extensive attention in the fields of organic synthesis and industrial chemistry. 3 )−H bonds through cheap, safe, and environmentally friendly conversion of oxygen sources into value-added products under mild conditions remains a challenging task in modern chemistry. Among the reported activation methods, three-dimensional (3D) metal-organic frameworks (MOFs) with ordered organic linkers and inorganic metal cluster nodes are considered to be a promising catalytic material. By integrating various functional units into a network structure, a fine-tuned catalytic platform is provided to achieve the cascade of multiple synergistic catalytic processes, which is difficult to achieve in other manifolds. Photoredox-mediated hydrogen atom transfer catalysis (HAT) has emerged as a promising strategy to directly activate and functionalize various C(sp 3 )−H bond. Ligand-metal charge transfer (LMCT) is a common photoexcitation mechanism that exists in high-valent transition metal complexes with empty valence shells, such as Cu II 、Ni II 、Ce IV , Fe III and Bi III , they can directly generate highly reactive free radicals from inert C(sp 3 )−H bonds. At the same time, reactive oxygen species (ROS) stand out due to their economic benefits and strong oxidative properties, such as singlet oxygen ( 1 O2) and superoxide radicals (O2 •− ). Recent progress has shown that the simultaneous integration of LMCT, HAT, and oxygen activation (EnT or PET) events into a single MOF reveals a promising approach to achieving inert C(sp 3 )−H bond activation and oxidation.
[0003] However, 3D MOFs suffer from pore size limitation, slow electron transfer, and substrate diffusion, which restrict their application in inert C(sp 3)−H bond oxidation. Meanwhile, in the past few decades, various two-dimensional (2D) layered nanocatalytic materials with ultrathin thickness (such as metal oxides and hydroxides, boron / carbon nitrides, graphene and graphene oxide, and transition metal dichalcogenides) have been developed as a powerful strategy to improve catalytic conversion efficiency and show surprising activity in photocatalytic activation and conversion. Because their high surface area and abundant accessible active sites enhance the communication between catalytic active sites and substrate molecules and minimize the pathways associated with mass / charge transfer. Ultrathin 2D MOF nanosheets formed by in situ exfoliation of 3D MOFs will provide more accessible active sites, ultrahigh flexibility, faster diffusion, and improve the host-guest affinity between active sites and substrate / product molecules within 2D MOF nanosheets. This method makes ultrathin 2D MOF nanosheets with HAT agents a promising candidate for promoting the photocatalytic activation and conversion of inert C(sp 3 )−H bond activation and transformation, which may help to develop MOF-based light-mediated HAT catalysts for opening the inert C(sp 3 )−H bonds provides a promising strategy. Although some ultrathin 2D MOF nanosheets have been constructed for specific catalytic transformations, to the best of our knowledge, few 2D MOF nanosheets synthesized from inexpensive raw materials have been used for inert C(sp 3 )−H bond activation and oxidation. Summary of the invention
[0004] In order to achieve the above purpose and solve the problems existing in the prior art, the technical solution adopted by the present invention is: a metal organic framework nanosheet with transition metal ions Cu 2+ As a node, L was used as a ligand to construct a three-dimensional layered metal organic framework material through a solvothermal synthesis strategy, and then a physical exfoliation technique was used to effectively prepare a metal organic framework nanosheet with high catalytic activity. The synthesis route is as follows: Cu 2+ +L→Cu-L The ligand L is selected from H2AQ; The transition metal salt is selected from copper nitrate; The ligand H2AQ has the following molecular structure formula (A): .
[0005] Specifically, a metal organic framework nanosheet is prepared by the following steps: dispersing a three-dimensional layered metal organic framework material Cu−AQ newly prepared by a solvothermal method using an inorganic copper salt and 2,7-dicarboxyanthraquinone in an organic solvent, ultrasonically obtaining a colloidal suspension, and then centrifuging or filtering and drying to obtain the metal organic framework nanosheet Cu−AQ-NS; The organic solvent is selected from at least one of ethylene glycol, acetonitrile and ethanol, and the dosage ratio of Cu-AQ to the organic solvent is 1 mg~4 mg:2 ml.
[0006] In some specific steps of preparing the metal organic framework nanosheets, the ultrasonication time is 6 to 48 h.
[0007] In some specific steps of preparing the metal organic framework nanosheets, the ultrasonication time is 6 to 36 h.
[0008] In some specific steps of preparing the metal organic framework nanosheets, the ultrasonic time is 20-30 h and the ultrasonic frequency is 50-60 KHz.
[0009] The metal organic framework nanosheet preparation steps of the present invention can obtain the metal organic framework nanosheet by centrifugation and filtration.
[0010] In some specific steps of preparing the metal organic framework nanosheets, the centrifugal speed is 6000-10000 rmp and the centrifugal time is 3-30 min.
[0011] In some specific steps of preparing the metal organic framework nanosheets, the centrifugal speed is 6000-10000 rmp and the centrifugal time is 4-10 min.
[0012] In some specific technical schemes, the preparation steps of the three-dimensional layered metal-organic framework material Cu-AQ are as follows: dissolving copper salt and 2,7-dicarboxyanthraquinone in an organic solvent, adding tetrafluoroboric acid, heating to 70-90 ºC in a high-pressure reactor for 3-5 hours, reacting for 15-30 hours, then cooling to room temperature for 15-30 hours, washing and drying to obtain Cu-AQ; The copper salt is selected from at least one of copper nitrate and copper perchlorate.
[0013] The organic solvent is selected from at least one of N,N-dimethylacetamide, N,N-dimethylacetamide, methanol and acetonitrile.
[0014] In some specific technical solutions, the mass ratio of copper salt to 2,7-dicarboxyanthraquinone is 1:1.5~2.0.
[0015] In some specific technical solutions, the usage ratio of tetrafluoroboric acid to organic solvent is 2 ul~3 ul:1 ml.
[0016] In some specific technical schemes, the preparation steps of the three-dimensional layered metal-organic framework material Cu−AQ are as follows: copper nitrate and 2,7-dicarboxyanthraquinone are dissolved in a mixed solution of N,N-dimethylformamide and acetonitrile in a volume ratio of 3:1 at a mass ratio of 1:1.6, tetrafluoroboric acid is added, and the temperature is raised to 80 ºC in a high-pressure reactor after 4 hours and reacted for 20 hours, then cooled to room temperature in 20 hours, washed and dried to obtain Cu−AQ.
[0017] The three-dimensional layered metal-organic framework material Cu−AQ of the present invention can be prepared by a method disclosed in the prior art, for example, referring to the literature Zhang Z, Yoshikawa H, Awaga K. Monitoring the solid-state electrochemistry of Cu (2, 7-AQDC)(AQDC= anthraquinone dicarboxylate) in alithium battery: coexistence of metal and ligand redox activities in a metal–organic framework[J]. Journal of the American Chemical Society, 2014, 136(46): 16112-16115.
[0018] A specific method for preparing a metal organic framework nanosheet comprises the following steps: Step 1: Add 10.8 g (0.1 mol) of benzyl alcohol dropwise to 150 mL of dry toluene under ice bath conditions and stir. Add 40.0 g (0.3 mol) of anhydrous aluminum chloride to the mixture and heat to 110°C for reflux reaction for 4 h. After cooling, add 25.0 g of crushed ice, 45 mL of water and 40 mL of concentrated hydrochloric acid to the reaction solution in sequence. After filtration, take the filter cake and wash it three times with 50 mL of water, 40 mL of ethyl acetate and 40 mL of saturated sodium carbonate solution in sequence. Place the crude product in an oven at 80°C and dry it to obtain a crude light yellow solid. The crude product was recrystallized with glacial acetic acid to obtain 4.5 g of a light gray product with a yield of 21.6%. Step 2: Dissolve 1.0 g of the light grey product obtained in step 1 in 150 mL of boiling glacial acetic acid, dissolve 1.0 g (10 mmol) of chromium trioxide in a small amount of water and slowly add it to the above solution, reflux for 30 to 40 min, and the solution turns green. After cooling, pour the reaction solution into a large amount of ice water and filter to obtain the product. Dry the crude product in a vacuum drying oven to obtain a milky white solid of about 1.1 g, with a yield of 93%; Step 3: Add 6.6 g (66 mmol) of chromium trioxide to a mixed solution of 0.3 mL of concentrated sulfuric acid, 1.8 mL of acetic anhydride and 40 mL of glacial acetic acid under ice bath conditions. Heat the mixed solution to 35 ºC, slowly add 1.3 g of the milky white solid obtained in step 2 to the mixed solution in several times, and after the addition is complete, raise the reaction temperature to 120 ºC and reflux for 4 h. After cooling to room temperature, pour the reaction solution into 400 mL of water and filter with suction. Take the upper filter cake and wash it with water to obtain a light yellow product, about 1.4 g, with a yield of 87%; Step 4: Dissolve 15.0 mg of the white powder obtained in step 3 and 24.0 mg of Cu(NO3)2·3H2O in a mixed solution of 3 mL of N,N-dimethylacetamide and 1 mL of acetonitrile, then add 10 uL of tetrafluoroboric acid to the clear solution by ultrasonic oscillation to completely dissolve it. Place the solution in a high-pressure reactor, heat it to 80 ºC over 4 h, keep it warm for 20 h, then cool it to room temperature for 20 h, collect it by filtration, wash the crystals with 5 mL of ethanol, and dry it to obtain blue-green block crystals. Step 5: Disperse 10.0 mg of the blue-green block crystals obtained in step 4 in 10 mL of ethylene glycol and ultrasonically treat at room temperature for about 24 h. Then, centrifuge the blue-green colloidal suspension at 8000 rpm for 5 min, and vacuum dry the obtained powder overnight to obtain Cu−AQ-NS (where Cu represents the metal node, AQ represents the anthraquinone ligand H2AQ, and NS represents the layered nanomaterial).
[0019] The metal organic framework nanosheet prepared by the method is used in catalyzing the coupling reaction of cyclohexane and benzylmalononitrile and catalyzing the aerobic oxidation reaction of cyclohexane.
[0020] The invention has the beneficial effects of: a preparation method of a metal organic framework nanosheet and its application, wherein the metal organic framework nanosheet is Cu in a transition metal salt 2+As a node, 2,7-dicarboxyanthraquinone is used as a ligand to prepare a metal organic framework material through a solvothermal reaction, and then a metal organic framework nanosheet is obtained by physical peeling; the two-dimensional copper-based MOF nanosheet prepared by the present invention combines the characteristics of hexagons and triangles to form a stable network structure. This network structure can not only effectively disperse external forces, but also provide strong support, greatly improve the structural stability of the MOF nanosheet, and ensure the porosity. At the same time, a large number of coordinated unsaturated copper sites provide a good environment for the LMCT process of Cu-Cl coordination. The peeled MOF nanosheet can expose more porous structures and sufficient anthraquinone active centers, which is conducive to the adsorption and conversion of oxygen, thereby generating sufficient active oxygen species and achieving higher catalytic activity. Compared with the existing technology, the metal organic framework nanosheet prepared by this method has low raw material price and high yield, and the obtained compound has stable chemical properties and is easy to put into practical applications. It can also efficiently catalyze the coupling reaction of cyclohexane and benzylidene malononitrile and catalyze the aerobic oxidation reaction of cyclohexane under mild light conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a structural diagram of the target compound Cu−AQ-NS of Example 3 of the present invention.
[0022] Figure 2 This is the XRD pattern of the target compound Cu−AQ-NS in Example 3 of the present invention.
[0023] Figure 3 This is the TEM image of the target compound Cu−AQ-NS of Example 3 of the present invention.
[0024] Figure 4 This is a curve chart showing the change in yield over time of the reaction of benzalkonium malononitrile and cyclohexane catalyzed by the target compound Cu-AQ-NS in Example 3 of the present invention under light irradiation conditions.
[0025] Figure 5 This is a cycle test diagram of the aerobic oxidation reaction of cyclohexane catalyzed by the target compound Cu-AQ-NS in Example 3 of the present invention under light conditions. DETAILED DESCRIPTION
[0026] The present invention will be further described below in conjunction with the embodiments. Example 1
[0027] Under ice bath conditions, benzyl alcohol (10.0 g, 0.1 mol) was added dropwise to 150 mL of toluene. After the addition was completed, anhydrous aluminum chloride (40.0 g, 0.3 mol) was added to the above mixed solution in small amounts and multiple times. After the addition was completed, the temperature of the mixture was gradually raised to room temperature, and stirred at room temperature for 30 minutes, and then heated to 110 °C for 3 h. After the reaction was completed and cooled to room temperature, the above reaction solution was slowly poured into an ice-water mixture, and 40 mL of concentrated hydrochloric acid was added to produce a yellow precipitate, which was filtered and washed three times with deionized water, ethyl acetate, saturated sodium carbonate solution and deionized water in sequence, dried to obtain a light yellow solid, and then recrystallized with glacial acetic acid to obtain 4.5 g of light yellow powder with a yield of 21.6% (based on the molar mass of benzyl alcohol), namely 2,7-dimethylanthracene; 1 H NMR (600 MHz, CDCl3, ppm): δ 8.36−8.16 (m, 2H), 7.88 (d,2H), 7.72 (s, 2H), 7.31−7.26 (m, 4H), 2.54 (s, 6H). Chromium trioxide (1.0 g, 10.0 mmol) and deionized water (1.0 g) were ultrasonically dissolved to prepare 1 mL of the first solution; 2,7-dimethylanthraquinone (1.0 g, 5 mmol) in the above step was added to 150 mL of glacial acetic acid, and the mixture was heated to 130 ºC until the solid was completely dissolved to prepare the second solution. The first solution was slowly added dropwise to the second solution, and then the solution turned dark green after reacting at 130 ºC for 45 minutes. After the reaction was stopped and the reaction temperature was cooled to room temperature, the solution was poured into 1000 mL of deionized water, and a white precipitate was precipitated by standing. The filter cake was vacuum filtered and washed with 300 mL of deionized water. The filter cake was vacuum dried to obtain 1.1 g of a white solid with a yield of 93%, i.e., 2,7-dimethylanthraquinone; 1 H NMR (600 MHz, CDCl3, ppm): δ 8.19 (d, 2H), 8.08 (d, 2H), 7.58 (dd, 2H), 2.53 (s, 6H). Chromium trioxide (6.6 g, 65.5 mmol) was added to a mixed solution of 0.3 mL of concentrated sulfuric acid, 1.8 mL of acetic anhydride and 40 mL of glacial acetic acid and placed at 0 ºC. Then the white solid of 2,7-dimethylanthraquinone (1.3 g, 5.4 mmol) obtained above was slowly added to the mixed solution. After the addition was completed, the reaction temperature was raised to 120 ºC and stirred for 5 h. The reaction was stopped and the reaction temperature was cooled to room temperature. The solution was poured into 500 mL of deionized water and allowed to stand to precipitate a yellow precipitate. The solution was vacuum filtered and the filter cake was washed with 300 mL of deionized water. The filter cake was vacuum dried to obtain 1.4 g of a bright yellow solid with a yield of 87%, i.e., the ligand H2AQ. 1 H NMR (600 MHz, DMSO- d 6, ppm): δ 13.75 (s, 1H), 8.69 (d, 2H), 8.43 (d, 2H), 8.34 (dd, 2H). Example 2
[0028] The organic ligand H2AQ (15.0 mg) and Cu(NO3)2·3H2O (24.0 mg) were added to a mixed solution of 3 mL N,N-dimethylacetamide and 1 mL acetonitrile and sonicated for 30 minutes to completely dissolve it. After the sonication, 10 μL HBF4 (40%) solution was added dropwise to the above clear solution, which was placed in a 25 mL high-pressure reactor and reacted in an oven at 80 °C for 20 h. After cooling to room temperature, green block crystals were obtained. The crystals were filtered out, washed three times with DMF and ethanol respectively, and dried at room temperature. The yield was 25% (calculated based on the molar mass of the ligand H2AQ). The crystal structure is shown in the figure below. Figure 1 shown. Example 3
[0029] Freshly prepared Cu−AQ (10.0 mg) was dispersed in ethylene glycol (10 mL) and ultrasonically treated at room temperature at a working frequency of 53 kHz for about 24 h. The blue-green colloidal suspension was then centrifuged at 8000 rpm for 5 minutes, and the obtained powder was vacuum dried overnight to obtain Cu−AQ-NS nanosheet material. The XRD pattern of the compound Cu−AQ-NS is shown in Figure 2 As shown. The TEM image of the compound Cu−AQ-NS is shown Figure 3 As shown. Figure 2 and 3 It can be seen that the expected single-layer nanosheets were successfully obtained through the exfoliation technique. Example 4
[0030] Freshly prepared Cu−AQ (10.0 mg) was dispersed in ethylene glycol (10 mL) and sonicated at room temperature at a frequency of 53 kHz for about 12 h. The blue-green colloidal suspension was then centrifuged at 8000 rpm for 5 min, and the resulting powder was vacuum dried overnight to obtain Cu−AQ-NS nanosheets. Example 5
[0031] Freshly prepared Cu−AQ (10.0 mg) was dispersed in ethylene glycol (10 mL) and sonicated at room temperature at a frequency of 53 kHz for about 6 h. The blue-green colloidal suspension was then centrifuged at 8000 rpm for 5 min, and the resulting powder was vacuum dried overnight to obtain Cu−AQ-NS nanosheets. Example 6
[0032] Freshly prepared Cu−AQ (10.0 mg) was dispersed in ethylene glycol (10 mL) and ultrasonically treated at room temperature at a working frequency of 53 kHz for about 36 h. The blue-green colloidal suspension was then centrifuged at 8000 rpm for 5 minutes, and the obtained powder was vacuum dried overnight to obtain Cu−AQ-NS nanosheet material. Example 7
[0033] Freshly prepared Cu−AQ (10.0 mg) was dispersed in ethanol (10 mL) and ultrasonically treated at room temperature at a working frequency of 53 kHz for about 24 h. The blue-green colloidal suspension was then centrifuged at 8000 rpm for 5 minutes, and the obtained powder was vacuum dried overnight to obtain Cu−AQ-NS nanosheet material. Example 8
[0034] Freshly prepared Cu−AQ (10.0 mg) was dispersed in acetonitrile (10 mL) and sonicated at 53 kHz for about 24 h at room temperature. The blue-green colloidal suspension was then centrifuged at 8000 rpm for 5 min, and the resulting powder was vacuum dried overnight to obtain Cu−AQ-NS nanosheets. Example 9
[0035] Freshly prepared Cu−AQ (10.0 mg) was dispersed in ethylene glycol (10 mL) and sonicated at room temperature at a frequency of 53 kHz for about 24 h. The blue-green colloidal suspension was then filtered and the obtained powder was vacuum dried overnight to obtain Cu−AQ-NS nanosheets.
[0036] Example 10: Coupling reaction of cyclohexane and benzylidenemalononitrile catalyzed by Cu−AQ-NS
[0037] In a 10 mL photoreaction tube, first add 3 mL of acetonitrile solution, then add 5.0 mg of Cu−AQ-NS, 2.0 mg of NH4Cl, 15.4 mg of benzylidene malononitrile and 10 μL of cyclohexane in sequence. Seal with a sealing stopper, pass argon for ten minutes to eliminate interference from other gases, seal with a sealing film after ventilation, and illuminate under a 420 nm band lamp for 6 hours. After the reaction is completed, use 1,3,5-trimethoxybenzene as an internal standard to calculate the yield. The result shows that benzylidene malononitrile is converted into 2-(cyclohexylphenylmethyl) malononitrile with a yield greater than 90%. Figure 4 shown.
[0038] Example 11: Aerobic oxidation of cyclohexane catalyzed by Cu−AQ-NS
[0039] In a 10 mL photoreaction tube, first add 3 mL of acetonitrile solution, then add 5.0 mg of Cu−AQ-NS, 2.0 mg of NH4Cl, 15.4 mg of benzylmalononitrile and 10 μL of cyclohexane in sequence. Seal with a sealing stopper, and pass oxygen for ten minutes to eliminate interference from other gases. After the ventilation is completed, connect an oxygen ball to the photoreaction tube to ensure oxygen supply. Irradiate under a 420 nm band lamp for 18 hours. After the reaction is completed, use 1,3,5-trimethoxybenzene as an internal standard to calculate the yield. The result shows that 60% of cyclohexane is converted into cyclohexanone, and the selectivity is greater than 97%. Figure 5 shown.
[0040] Example 12: Coupling reaction of cyclohexane with benzylidenemalononitrile and aerobic oxidation reaction of cyclohexane catalyzed by Cu-AQ-NS prepared in Example 4-9 The catalytic effect of the Cu-AQ-NS prepared in Examples 4-9 on the coupling reaction of cyclohexane with benzalmalononitrile and the aerobic oxidation reaction of cyclohexane was studied by referring to the methods of Examples 10 and 11. The specific data are shown in Tables 1 and 2.
[0041] Table 1 Data of the coupling reaction of cyclohexane and benzylidenemalononitrile catalyzed by Cu-AQ-NS prepared in Example 3-8
[0042] Table 2 Data of aerobic oxidation of cyclohexane catalyzed by Cu-AQ-NS prepared in Examples 3-8
[0043] It can be seen from the data in Tables 1 and 2 that the Cu−AQ-NS prepared in Example 3-9 has a good catalytic effect on the coupling reaction of cyclohexane with benzylmalononitrile and the aerobic oxidation reaction of cyclohexane.
[0044] The invention has the advantages that the raw materials of the metal organic framework material prepared by the method are low in price and high in yield, the obtained compound has stable chemical properties and is easy to put into practical application. As a catalyst, it can be used for in-situ catalytic oxidation of alkane cyclohexane under light conditions and has a high catalytic conversion efficiency.
Claims
1. A metal organic framework nanosheet, characterized in that: The preparation is carried out by the following steps: dispersing the three-dimensional layered metal organic framework material Cu−AQ newly prepared by the solvothermal method of inorganic copper salt and 2,7-dicarboxyanthraquinone in an organic solvent, ultrasonically obtaining a colloidal suspension, and then centrifuging or filtering and drying to obtain the metal organic framework nanosheet Cu−AQ-NS; The organic solvent is selected from at least one of ethylene glycol, acetonitrile and ethanol, and the dosage ratio of Cu-AQ to the organic solvent is 1 mg~4 mg:2 ml.
2. The metal organic framework nanosheet according to claim 1, characterized in that: The ultrasound time is 6 to 48 hours.
3. The metal organic framework nanosheet according to claim 1, characterized in that: The ultrasound time was 6 to 36 h.
4. The metal organic framework nanosheet according to claim 1, characterized in that: The ultrasound time was 20-30 h, and the ultrasound frequency was 50-60 kHz.
5. The metal organic framework nanosheet according to any one of claims 1 to 4, characterized in that: The centrifugal speed is 6000~10000 rmp and the centrifugal time is 3~30 min.
6. The metal organic framework nanosheet according to any one of claims 1 to 4, characterized in that: The preparation steps of the three-dimensional layered metal-organic framework material Cu-AQ are as follows: dissolving copper salt and 2,7-dicarboxyanthraquinone in an organic solvent, adding tetrafluoroboric acid, heating to 70-90 ºC in a high-pressure reactor for 2-5 hours, reacting for 15-30 hours, then cooling to room temperature within 15-30 hours, washing and drying to obtain Cu-AQ; The copper salt is selected from at least one of copper nitrate and copper perchlorate; The organic solvent is selected from at least one of N,N-dimethylacetamide, N,N-dimethylacetamide, methanol and acetonitrile.
7. The metal organic framework nanosheet according to claim 6, characterized in that: The mass ratio of copper salt to 2,7-dicarboxyanthraquinone is 1:1.5~2.0, and the amount ratio of tetrafluoroboric acid to organic solvent is 2 ul~3 ul:1 ml.
8. The metal organic framework nanosheet according to claim 7, characterized in that: The preparation steps of the three-dimensional layered metal-organic framework material Cu−AQ are as follows: copper nitrate and 2,7-dicarboxyanthraquinone are dissolved in a mixed solution of N,N-dimethylformamide and acetonitrile in a volume ratio of 3:1 at a mass ratio of 1:1.6, tetrafluoroboric acid is added, and the temperature is raised to 80 ºC in a high-pressure reactor after 4 hours for reaction for 20 hours, then cooled to room temperature in 20 hours, washed and dried to obtain Cu−AQ.
9. Use of the metal organic framework nanosheet according to any one of claims 1 to 4 in catalyzing the coupling reaction of cyclohexane and benzylmalononitrile.
10. Use of the metal organic framework nanosheet according to any one of claims 1 to 4 in catalyzing aerobic oxidation of cyclohexane.
Citation Information
Patent Citations
PEG-modified two-dimensional nanosheet photothermal conversion material and application thereof
CN107625962A
Synthesis method and application of bifunctional metal-organic framework for selective oxidation of inert C-H bonds
CN114891231A
Anthraquinone-based two-dimensional MOF photocatalyst as well as preparation method and application thereof
CN117700766A